1983
DOI: 10.1111/j.1471-4159.1983.tb13584.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute and Chronic Cholinesterase Inhibition with Diisopropylfluorophosphate on Muscarinic, Dopamine, and GABA Receptors of the Rat Striatum

Abstract: The effects of acute and chronic administration of diisopropylfluorophosphate (DFP) to rats on acetylcholinesterase (AChE) activity (in striatum, medulla, diencephalon, cortex, and medulla) and muscarinic, dopamine (DA), and gamma-aminobutyric acid (GABA) receptor characteristics (in striatum) were investigated. After a single injection of (acute exposure to) DFP, striatal region was found to have the highest degree of AChE inhibition. After daily DFP injections (chronic treatment), all brain regions had the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“…We reported that the changes in dopaminergic system arose secondarily to an elevation of brain acetylcholine following cholinesterase inhibition [17,18]. Chronic administration of DFP reduced the number of muscarinic sites, but increased dopamine and GABA receptor densities [17]. Further, a decrease in dopamine level at striatum was detected after both acute and chronic exposure to DFP [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that the changes in dopaminergic system arose secondarily to an elevation of brain acetylcholine following cholinesterase inhibition [17,18]. Chronic administration of DFP reduced the number of muscarinic sites, but increased dopamine and GABA receptor densities [17]. Further, a decrease in dopamine level at striatum was detected after both acute and chronic exposure to DFP [18].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in this lab already addressed the involvement of other neurotransmitter systems, dopaminergic and GABAergic system) in OP antiAChE-induced neurotoxicity. We reported that the changes in dopaminergic system arose secondarily to an elevation of brain acetylcholine following cholinesterase inhibition [17,18]. Chronic administration of DFP reduced the number of muscarinic sites, but increased dopamine and GABA receptor densities [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although at least part of the explanation for the occurrence of tolerance to tabun in rats should be found in its metabolism (31), there is no doubt that the other part should rest on the grounds of desensitisation and down-regulation cholinergic and probably some other brain receptors (32).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] On long-term exposure, some organophosphorus compounds, such as diisopropylfluorophosphate caused significant changes of GABA A receptor following 14 days of treatment. 20) The foregoing evidences indicate that the effects produced by organophosphates include a variety of behavioral and neurological manifestations, all of which can not be attributed to cholinergic hyperactivity solely. Other systems may, in addition or independently, be involved in OPs intoxicatin.…”
Section: Introductionmentioning
confidence: 99%
“…Other systems may, in addition or independently, be involved in OPs intoxicatin. 20,21) Since the alterations of GABAergic system on OPs pesticides intoxication process remains obscured, more remedial approaches are needed to understand the GABAergic mechanisms involved in OPs intoxication. The present paper investigates the alterations of GABAergic system in rat cortex consequent to acute and subchronic dimethoate administration to explore the role of the IAA system in OPs poisoning.…”
Section: Introductionmentioning
confidence: 99%